Mental health distress and associated factors among HIV- positive adolescents attending ART Clinics in Nigeria - Adebayo Akadri; Akinmade Adepoju; Olabisi Bamidele; Temitayo Oluwole; Kolawole Sodeinde; Olumide Abiodun (Elsevier, 2024)
Background: Mental health disorders may have a negative influence on health outcomes in patients with HIV; however, these conditions are under-diagnosed among adolescents living with HIV. This study aimed to assess the prevalence of mental health distress and associated factors among adolescents living with HIV attending Antiretroviral Therapy clinics in Nigeria. Methods: This was a cross-sectional study of 212 HIV-infected adolescents attending routine HIV clinic visits across five high patient-density clinics in southwestern Nigeria. Mental health distress was assessed using the General Health Questionnaire-12 (GHQ-12) and data was analyzed using IBM-SPSS Statistics for Windows version 22.0 (IBM Corp., Armonk, NY, USA). Results: The prevalence of mental health distress among participants was 34.9 %. On bivariate analysis, respondents who consumed alcohol sometimes had significantly higher mental health scores than those who never took alcohol (t-test 2.738; P = 0.007). There were no significant differences in the mean mental health scores of respondents with regards to social factors (smoking, experience of rape, disability status, mode of payment for health services, and number of living companions) and clinical factors (duration of diagnosis and treatment of HIV, the type of HAART regimen, and whether there had been a change in regimen). On multivariate analysis no social or clinical factor was found to be independently associated with mental health distress. Conclusions: The prevalence of mental health distress among adolescents living with HIV in southwestern Nigeria is high. Respondents who consumed alcohol had significantly higher mental health scores than those who never took alcohol. Future studies should explore psychosocial stressors that could be determinants of mental health distress among adolescents living with HIV in Nigeria.